1990
DOI: 10.1002/arch.940140402
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine interrelationship between the parasitoid Chelonus sp. and its host Trichoplusia ni

Abstract: The egg-larval parasitoid Chelonus sp. induces the precocious onset of metamorphosis in the 4th (penultimate) stadium of its host Trichoplusia ni, emerges from the prepupa, and then feeds on it. Qualitative and quantitative changes in ecdysteroids and juvenile hormone were measured. Hemolymph of 3rd-to 4th-instar host larvae and the parasitoids they contained, as well as nonparasitized and parasitized eggs, were analyzed. In the host hemolymph a broad peak of ecdysteroids during molting into the 4th stadium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Results from other studies also demonstrated that parasitism contributed to the ecdysteroid alteration (Grossniklaus-Bürgin and Lanzrein, 1990;Gelman et al, 1998;Grossniklaus-Bürgin et al, 1998). Our results support the idea that venom from P. puparum influences the endocrine system of P. rapae pupae.…”
Section: Discussionsupporting
confidence: 92%
“…Results from other studies also demonstrated that parasitism contributed to the ecdysteroid alteration (Grossniklaus-Bürgin and Lanzrein, 1990;Gelman et al, 1998;Grossniklaus-Bürgin et al, 1998). Our results support the idea that venom from P. puparum influences the endocrine system of P. rapae pupae.…”
Section: Discussionsupporting
confidence: 92%
“…fourth instars parasitized by A. reticulatus increased dramatically 12 h before egression of parasitoids. The hemolymph titer of juvenile hormone (JH) II in the fourth instars of Trichoplusia ni parasitized by Chelonus sp., belonging to the same subfamily (Cheloninae) as A. reticulatus, falls to undetectable levels shortly before emergence of the parasitoid larvae, whereas 20-hydroxyecdysone titer increases before emergence of the parasitoid larvae (Grossniklaus-Bürgin & Lanzrein, 1990). In both cases, the parasitized host larvae exhibit precocious metamorphosis during the fourth instar.…”
Section: Discussionmentioning
confidence: 97%
“…Alterations in JH and ecdysteroid titers during the host egg stage have been reported during parasitism by the egglarval parasitoid Chelonus sp. [26], but these changes were not reported to be associated with any parasitoid embryonic event. Studies have also suggested that ecdysteroids and JH enhance the in vitro growth of the polyembryonic encyrtid Ageniuspis fuscicollis although specific developmental roles for hormones were not defined [30].…”
Section: Discussionmentioning
confidence: 90%